Irrational thoughts and their relation to the psychological stress among mothers of children with an autism spectrum disorder in Al Majma'ah governorate - Alotaibi, Manar Sayer (Journal of Educational and Psychological Sciences, 2025)
This study aimed to identify the degree of irrational thoughts and the degree of psychological stress among mothers of children with an autism spectrum disorder in AI Majma'ah Governorate and reveal the relationship between them and find out if there are differences due to the following variables: a mother's age- educational level – economic level, and the study used the descriptive approach. The sample consisted of 43 mothers of children with an autism spectrum disorder in Al Majma'ah Governorate. The tools used included the scale of irrational thoughts prepared by Abu Rumman (2005) and the psychological stress scale prepared by Jaber (2008). The study achieved the following results: The degree of irrational thoughts among mothers of children with an autism spectrum disorder in Al Majma'ah Governorate is high, the degree of psychological stress for them was moderate, and there is a positive correlation with statistical significance between irrational thoughts and psychological stress among mothers of children with an autism spectrum disorder in AI Majma'ah Governorate. As the results showed, there are not statistically significant differences in the degree of irrational thought and psychological stress among mothers of children with an autism spectrum disorder in Al Majma'ah Governorate due to the variables (age, educational level, economic level) and the study ended with a few recommendations among them is activating the role of the media in educating families about their mental health and its impact on their children.
Keywords: Irrational thoughts; Psychological stress; Mothers of children with an autism spectrum disorder; AI Majma'ah governorate